Chapter F of the International Code of Nomenclature for algae, fungi, and plants as approved by the 11th International Mycological Congress, San Juan, Puerto Rico, July 2018 - Tom W. May; Scott A. Redhead; Konstanze Bensch; David L. Hawksworth; James Lendemer; Lorenzo Lombard; Nicholas J. Turland (IMA Fungus, 2019)
Abstract A revised version of Chapter F of the International Code of Nomenclature for algae, fungi, and plants is presented, incorporating amendments approved by the Fungal Nomenclature Session of the 11th International Mycological Congress held in San Juan, Puerto Rico in July 2018. The process leading to the amendments is outlined. Key changes in the San Juan Chapter F are (1) removal of option to use a colon to indicate the sanctioned status of a name, (2) introduction of correctability for incorrectly cited identifiers of names and typifications, and (3) introduction of option to use name identifiers in place of author citations. Examples have been added to aid the interpretation of new Articles and Recommendations, and Examples have also been added to the existing Art. F.3.7 concerning the protection extended to new combinations based on sanctioned names or basionyms of sanctioned names (which has been re-worded), and to Art. F.3.9 concerning typification of names accepted in the sanctioning works.